Configurational analysis of inbound and outbound innovation impact on competitive advantage in the smes of the Portuguese hospitality sector - Jorge de Andrés Sánchez; Francisco Musiello-Neto; Orlando Manuel Martins Marques de Lima Rua; Mario Arias-Oliva (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study analyzes the effects of inbound and outbound open innovation, along with organizational strategy and corporate risk management, on competitive advantage and disadvantage in the Portuguese hospitality sector's cost, service, and product. We use a quantitative approach based on fuzzy set qualitative comparative analysis (fsQCA) of survey data from 251 executive directors of hotels from Portuguese small and medium-sized enterprises (SMEs). The results allow visualization of the interactions of inbound and outbound open innovation with corporate risk management and organizational strategy in order to generate competitive advantage. The results demonstrate that corporate risk management is a keystone for a competitive cost advantage, whereas inbound open innovation plays a fundamental role in obtaining competitive advantages for products and services. Other factors, such as outbound open innovation or those linked with organizational strategy, have less impact, and/or the sign of their influence depends on the configuration of the remaining variables.
Keywords: 650; competitive advantage; configurational analysis; corporate risk management; fuzzy set qualitative comparative analysis; hotel industry; inbound open innovation; organizational strategy; outbound open innovation